2013
DOI: 10.1097/pcc.0b013e3182720fab
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes of Unplanned PICU Postoperative Admissions

Abstract: Airway abnormality, anesthetic factors, and hypoxia intraoperative were risk factors associated with UIA. Although preventable events contribute significantly to unplanned PICU admissions, they constitute a room of opportunity in quality improvement programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 20 publications
2
50
1
Order By: Relevance
“…These patients were not obese and, in those who had preoperative polysomnogram, the degree of OSA was usually not severe. Although no true risk‐adjusted benchmark for UIAs is established in children, UIA rates have been described in the literature to range from 0.06% to 2.6% . Because the overall rate of UIA at our institution after T&A is 0.21%, these miscalculations represent the unpredictable nature of this population rather than poor preoperative planning.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These patients were not obese and, in those who had preoperative polysomnogram, the degree of OSA was usually not severe. Although no true risk‐adjusted benchmark for UIAs is established in children, UIA rates have been described in the literature to range from 0.06% to 2.6% . Because the overall rate of UIA at our institution after T&A is 0.21%, these miscalculations represent the unpredictable nature of this population rather than poor preoperative planning.…”
Section: Discussionmentioning
confidence: 94%
“…Although no true risk-adjusted benchmark for UIAs is established in children, UIA rates have been described in the literature to range from 0.06% to 2.6%. [9][10][11] Because the overall rate of UIA at our institution after T&A is 0.21%, these miscalculations represent the unpredictable nature of this population rather than poor preoperative planning. In comparing patients utilizing ICU resources to those for whom resources were not necessary, our cohort demonstrated an association between resource need and young age, neurological/neuromuscular comorbidity, and gastrostomy tube status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] Early identification of indicators predicting postoperative adverse events, such as longer hospital stay, disability, and death, would prevent unfavorable consequences. [ 6 7 ] The present audit was conducted to recognize the causes of postoperative SICU admissions, to identify accountable peri-operative factors, and to determine the outcomes in terms of mortality, morbidity, SICU stay, and discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified airway procedures, higher American Society of Anesthesiologists Classification (ASA) score, longer anesthesia time, multiple procedures, and infants less than 1 year of age as risk factors for unanticipated ICU admissions in postoperative pediatric patients. [8][9][10] As patients receiving care from pediatric otolaryngologists frequently have these risk factors, there is uncertainty of the patient's true postoperative risk. Uncertainty often drives the surgeon to "err on the side of caution" and request an ICU bed if a patient is at risk for unanticipated ICU admission.…”
Section: Introductionmentioning
confidence: 99%